Pengaruh Retensi dan Kompetensi Terhadap Kinerja Karyawan PT. Taspen (Persero) Kantor Cabang Malang - Norma Erlinda; Dianawati Suryaningtyas; Arien Anjar Puspitosari Suharso (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2019)
The purpose of this study was to determine the effect of retention and competence on employee performance at PT. Taspen (Persero) KC Malang. The independent variable in retention and competence research, then the dependent variable is employee performance. This research was conducted at PT.Taspen (Persero) Malang Branch Office, the sample in this study were 40 respondents. The sampling technique in this study uses saturated samples. The analysis technique used in this study is Multiple Linear Regression. Based on research that has been done the results show that retention and competence have a partial and simultaneous effect on employee performance.